(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article is devoted to the analysis of credit institution stability and includes several variants of methods, which have been developed by supervision authorities and international financial rating agencies and central banks of developed countries. It is emphasized that today there are no unified and generally accepted methods for estimation of financial stability of commercial banks.